2001
DOI: 10.1002/1521-3935(20011201)202:18<3513::aid-macp3513>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Photopolymerization Reactions Initiated by a Visible Light Photoinitiating System: Dye/Amine/Bis(trichloromethyl)-Substituted-1,3,5-Triazine

Abstract: Addition of a bis(trichloromethyl)‐substituted‐1,3,5‐triazine (Tz) to a dye/amine photoinitiating system leads clearly to an increased efficiency of polymerization under visible light irradiation. The polymerization rates obtained with three triazine derivatives with either phenosafranine, eosin or Rose Bengal as light absorbing species, were measured. Whatever the investigated dye/amine mixture, the addition of Tz led to a strong synergistic effect: the inhibition time decreased and the polymerization rate in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 21 publications
6
66
0
Order By: Relevance
“…To the contrary, a real progress has been made in the synthesis of new chemical skeletons and new modifications of existing structures, as well as in the use of new additives: this has allowed the proposal of a large number of novel PIs and PISs. The mechanisms encountered in these systems are schematically depicted in reactions (1)-(7) [10][11][12][13][14][15][16]: after light absorption, PI interacts with one or two additives (e.g., iodonium salt, amine, N-vinylcarbazole, silane, chloro triazine, etc. ; Scheme 1) to generate initiating radicals for free radical polymerization (FRP; reactions (1)-(3a) and (6)) of (meth)acrylates or thiol-ene polymerization (TEP; reactions (1), (2) and (5)), cations or radical cations for cationic polymerization (CP; reactions (1) and (2)) or free radical promoted cationic polymerization (FRPCP) of epoxides (reactions 1-3) or vinyl ethers (reactions (1), (2) and (4)); the concomitant cationic/radical polymerization CCRP (hybrid cure) of a cationic monomer/radical monomer blend can also be achieved for the manufacture of interpenetrated polymer networks IPNs.…”
Section: Introductionmentioning
confidence: 99%
“…To the contrary, a real progress has been made in the synthesis of new chemical skeletons and new modifications of existing structures, as well as in the use of new additives: this has allowed the proposal of a large number of novel PIs and PISs. The mechanisms encountered in these systems are schematically depicted in reactions (1)-(7) [10][11][12][13][14][15][16]: after light absorption, PI interacts with one or two additives (e.g., iodonium salt, amine, N-vinylcarbazole, silane, chloro triazine, etc. ; Scheme 1) to generate initiating radicals for free radical polymerization (FRP; reactions (1)-(3a) and (6)) of (meth)acrylates or thiol-ene polymerization (TEP; reactions (1), (2) and (5)), cations or radical cations for cationic polymerization (CP; reactions (1) and (2)) or free radical promoted cationic polymerization (FRPCP) of epoxides (reactions 1-3) or vinyl ethers (reactions (1), (2) and (4)); the concomitant cationic/radical polymerization CCRP (hybrid cure) of a cationic monomer/radical monomer blend can also be achieved for the manufacture of interpenetrated polymer networks IPNs.…”
Section: Introductionmentioning
confidence: 99%
“…It has three main advantages: (i) the fundamental state of the PI is regenerated and can participate to a new cycle, (ii) supplementary initiating radicals are produced, (iii) potential terminating agents are consumed. Among the numerous PCIS redox additives reported in the literature, triazine derivatives (Tz) have been extensively used as electronacceptors in combination with amines, [12][13][14][15][16][17] thiols, [18] or borate salts. [18][19][20][21] They have been found to enhance final conversion and rate of polymerization by reacting with the semi-reduced form of the PI.…”
Section: Dedicated To Yusuf Yagci On the Occasion Of His 65th Annivermentioning
confidence: 99%
“…It has been reported that triazine A (TA) is not able to initiate acrylate photopolymerization when combined to several different dyes. [12,13] However, recent studies have proved that triazine derivatives are actually efficient to act as co-initiators, via a photoinduced electron transfer from the singlet state of pyrromethene derivatives. [15][16][17] Interestingly, isopropylthioxanthone (ITX) which is one of the most versatile photoinitiator for free radical photopolymerization (FRP) [23] has never been combined with triazine derivatives in a two-component photoinitiating system for FRP, although that such a combination has been studied for photoacid generation.…”
Section: Dedicated To Yusuf Yagci On the Occasion Of His 65th Annivermentioning
confidence: 99%
See 2 more Smart Citations